2007
DOI: 10.1021/jp073188i
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Stability of the [TCNE]22-Dimers in Dichloromethane Solution:  A Computational Study

Abstract: The solution behavior of [TCNE](.-), which forms long-living pi-[TCNE]22- dimers, is computationally studied by B3LYP and MCQDPT/CASSCF(2,2) calculations (a multiconfigurational quasi-degenerate perturbative calculation using a CASSCF(2,2) wavefunction, which properly accounts for the dispersion interaction). B3LYP calculations indicate minimum-energy [TCNE](2)(2-)(dichloromethane)(4) aggregates, a solvent where pi-[TCNE](2)(2-) dimers are spectroscopically observed. Their existence is attributed to [TCNE](.-)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 32 publications
1
61
0
Order By: Relevance
“…52-54), but, sometimes, it presents certain limitations, specially for the simulation of π interactions, where it can overestimate the interaction energy, specially in cases where a small basis set has been used (smaller than triple zeta). [55][56][57] The use of a most precise method such as Coupled-Cluster Singles Doubles and Non-iterative Triples Correction (CCSD(T)) 58 [28][29][30][31]40 depending on the quality of the exchangecorrelation functional, such as the description of transition metals, thermochemical properties, medium-range correlation energy, barrier heights or non-covalent bond interactions. Among all those, the former is the one in which we would like to focus our interest in this work.…”
Section: A Methodologymentioning
confidence: 99%
“…52-54), but, sometimes, it presents certain limitations, specially for the simulation of π interactions, where it can overestimate the interaction energy, specially in cases where a small basis set has been used (smaller than triple zeta). [55][56][57] The use of a most precise method such as Coupled-Cluster Singles Doubles and Non-iterative Triples Correction (CCSD(T)) 58 [28][29][30][31]40 depending on the quality of the exchangecorrelation functional, such as the description of transition metals, thermochemical properties, medium-range correlation energy, barrier heights or non-covalent bond interactions. Among all those, the former is the one in which we would like to focus our interest in this work.…”
Section: A Methodologymentioning
confidence: 99%
“…Calculations indicate that in the case of TCNE •− , for example, solvation has an important role to play in stabilising the dimer pair. 10 Similarly solvent dependent studies on TTF •+ have revealed H dim in the region -16 to -38 kJmol −1 reflecting the important role of solvation effects on stabilising/destabilising the dimer. In other cases it may be likely that ion pairing can play an important role in stabilising such dimers.…”
Section: Computational Studies On Dimerisationmentioning
confidence: 97%
“…Long, multicenter CÀC bonds within dimers of neutral or charged radicals, for example, p-[TCNE] 2 2À (TCNE = tetracyanoethylene, Figure 1) have been established from spectroscopic (UV/Vis/NIR, ESR, NMR and IR) studies, structural (crystallographic) evidence, and theoretical support. [1][2][3][4][5][6][7][8] [TCNE] 2 2À is stable in the solid state as a consequence of the attractive cation + ···anion À interactions exceeding the repulsive cation + ···cation + and [TCNE]C À… [TCNE]C À interactions, and is assisted by the dispersion and bonding energetic components acting between the two [TCNE]C À fragments. [6,8] Thus, p-[TCNE] 2 2À anion is diamagnetic, and has an observed closed-shell singlet ground state.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] [TCNE] 2 2À is stable in the solid state as a consequence of the attractive cation + ···anion À interactions exceeding the repulsive cation + ···cation + and [TCNE]C À… [TCNE]C À interactions, and is assisted by the dispersion and bonding energetic components acting between the two [TCNE]C À fragments. [6,8] Thus, p-[TCNE] 2 2À anion is diamagnetic, and has an observed closed-shell singlet ground state. Its long multicenter bond is best described as a two-electron/four-center (2e À /4c) bond, [1,8] with an approximately 2.9 intradimer separation.…”
mentioning
confidence: 99%
See 1 more Smart Citation